The Protective Role of Mitochondrial Ferritin on Erastin-Induced Ferroptosis - Wang, Yue-Qi; Chang, Shi-Yang; Wu, Qiong; Gou, Yu-Jing; Jia, Linpei; Cui, Yan-Mei; Yu, Peng; Shi, Zhen-Hua; Wu, Wen-Shuang; Gao, Guofen; Chang, Yan-Zhong (Frontiers in Aging Neuroscience, 2016)
Ferroptosis, a newly identified form of regulated cell death, is characterized by overwhelming iron-dependent accumulation of lethal lipid reactive oxygen species (ROS). Preventing cellular iron overload by reducing iron uptake and increasing iron storage may contribute to inhibit ferroptosis. Mitochondrial ferritin (FtMt) is an iron-storage protein that is located in the mitochondria, which has a significant role in modulating cellular iron metabolism. Recent studies showed that FtMt played inhibitory effects on oxidative stress-dependent neuronal cell damage. However, the potential role of FtMt in the progress of ferroptosis in neuronal cells has not been studied. To explore this, we established ferroptosis models of cell and drosophila by erastin treatment. We found that overexpression of FtMt in neuroblastoma SH-SY5Y cells significantly inhibited erastin-induced ferroptosis, which very likely was achieved by regulation of iron homeostasis. Upon erastin treatment, significant increases of cellular labile iron pool (LIP) and cytosolic ROS were observed in wild-type SH-SY5Y cells, but not in the FtMt-overexpressed cells. Consistent with that, the alterations of iron-related proteins in FtMt-overexpressed cells were different from that of the control cells. We further investigated the role of FtMt in erastin-induced ferroptosis in transgenic drosophila. We found that the wild-type drosophilas fed an erastin-containing diet didn’t survive more than three weeks. In contrast, the FtMt overexpressing drosophilas fed the same diet were survival very well. These results indicated that FtMt played a protective role in erastin-induced ferroptosis.